2022
DOI: 10.1111/jnu.12853
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19: Implications for Nursing and Health Care in the United States

Abstract: PurposeCOVID‐19 and other recent infectious disease outbreaks have highlighted the urgency of robust, resilient health systems. We may now have the opportunity to reform the flawed health care system that made COVID‐19 far more damaging in the United States (U.S.) than necessary.Design and MethodsGuided by the World Health Organization (WHO) Health System Building Blocks framework (WHO, 2007) and the socio‐ecological model (e.g., McLeroy et al., 1988), we identified challenges in and strengths of the U.S.’ han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…While clinicians in addiction treatment in Ukraine maintain the continuity of OAT programs thanks to their deeply rooted professional identity and unique organizational culture despite the destruction and plummeting resources, assistance and respite is urgently needed – and it is not yet too late to provide it. This question also matters to the US, given healthcare staff shortages and a high rate of burnout ( 46 , 47 ) during Covid-19 particularly among nurses ( 48–51 ), yet the government provided little response ( 52 , 53 ), leaning into traditional expectations of healthcare staff sacrifice ( 54 ). The key learning from our pre-crisis research suggests that in low and middle-income countries like Ukraine, humanitarian crises strain already limited resources, leaving essential healthcare workers overlooked ( 5 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…While clinicians in addiction treatment in Ukraine maintain the continuity of OAT programs thanks to their deeply rooted professional identity and unique organizational culture despite the destruction and plummeting resources, assistance and respite is urgently needed – and it is not yet too late to provide it. This question also matters to the US, given healthcare staff shortages and a high rate of burnout ( 46 , 47 ) during Covid-19 particularly among nurses ( 48–51 ), yet the government provided little response ( 52 , 53 ), leaning into traditional expectations of healthcare staff sacrifice ( 54 ). The key learning from our pre-crisis research suggests that in low and middle-income countries like Ukraine, humanitarian crises strain already limited resources, leaving essential healthcare workers overlooked ( 5 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“… 40 , 41 , 42 For example, in the US, UK and Australia the increased load in the healthcare systems during COVID‐19 for crucial care, and subsequently high costs, led to job cuts and high levels of resignations for highly experienced nurses. 43 , 44 , 45 Funds for professional development were cut and redirected to the COVID‐19 response 46 ; the opportunities for education and career progress were reduced. 44 The consequences of cuts like these are under‐explored in Australia, but they are likely similar.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are not novel in the context of nursing at the time of COVID‐19 40–42 . For example, in the US, UK and Australia the increased load in the healthcare systems during COVID‐19 for crucial care, and subsequently high costs, led to job cuts and high levels of resignations for highly experienced nurses 43–45 . Funds for professional development were cut and redirected to the COVID‐19 response 46 ; the opportunities for education and career progress were reduced 44 .…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of the pandemic, healthcare systems worldwide were chaotically responding to the outbreak and its consequences. 33 While healthcare is mostly focused on providing proper treatment to infected patients, soon after, healthcare managers recognized that existing intervention policies are not serving their purpose. 34 Our data showed that international periodicals served as a source of COVID-19 data input for local and regional COVID-19 news.…”
Section: Discussionmentioning
confidence: 99%